On the Usage of Locally Dense Basis Sets in the Calculation of NMR Indirect Nuclear Spin–Spin Coupling Constants: Vicinal Fluorine–Fluorine Couplings - Sánchez, Marina (2005)
Locally dense basis set were developed for correlated ab initio calculations of vicinal fluorine  fluorine indirect nuclear spin spin couplings in several saturated and unsaturated fluorinated hydrocarbons. We find that the choice of the basis set for each atom belonging to our studied model compounds depends on its location with respect to the coupled fluorine atoms and on the cis/trans or synperiplanar/antiperiplanar conformation of the molecule. Carbon atoms in the bonding path connecting the coupled fluorine atoms have to be described with better basis sets than the carbon atoms outside this path. For the hydrogen atoms directly connected to the coupling pathway in molecules with trans or antiperiplanar conformations and for all hydrogen atoms not directly connected to the coupling pathway one can employ a minimal basis set with only one s-function. Employing these type of LDBSs we can reduce the number of necessary basis functions by about 30% without losing more than about 1 Hz in accuracy. The analysis of the four contributions to the vicinal fluorine fluorine coupling constants shows that the non-contact orbital paramagnetic term is the most important contribution followed by the also non-contact spin-dipolar term. The Fermi contact term is the largest contribution only in the synperiplanar conformations of 1,2-difluoroethane and -propane.